Pengembangan Media Pembelajaran Operasi Bilangan Bulat Berbasis Permainan Flashcard (Integer Clash) untuk Meningkatkan Motivasi Belajar Siswa - Musriyani, Iin; Mujiastutik, Dhea Putri; Darmadi, Darmadi; Astuti, Indra Puji (Universitas Nusantara PGRI Kediri, 2025)
This study aims to develop a flashcard game-based learning media called Integer Clash, which is designed to increase students' learning motivation in understanding the concept of integer operations. This media combines elements of educational games with an interactive approach, so as to create a fun and challenging learning atmosphere. The research method used is research and development. Product trials were conducted on elementary school students with data collection through observation and interviews. The results showed that the use of Integer Clash as a learning media was able to significantly increase students' learning motivation. In addition, students showed high enthusiasm in participating in learning. Based on these findings, Integer Clash can be used as an alternative effective learning media in supporting the teaching and learning process of mathematics, especially on integer operations material.